1995
DOI: 10.1289/ehp.95103s9103
|View full text |Cite
|
Sign up to set email alerts
|

Dermal exposure to environmental contaminants in the Great Lakes.

Abstract: This paper reviews the literature to determine the importance of the dermal route of exposure for swimmers and bathers using Great Lakes waters and summarizes the chemical water contaminants of concern in the Great Lakes along with relevant dermal absorption data. We detail in vivo and in vitro methods of quantifying the degree of dermal absorption and discuss a preference for infinite dose data as opposed to finite dose data. The basic mechanisms of the dermal absorption process, routes of chemical entry, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…On the basis of a maximum phenanthrene concentration of 6 μg/L in drinking water (Table 2) and a surface body area of 18,000 cm 2 , we calculated that 30 min of daily bathing or showering would result in a dermally absorbed phenanthrene dose of only 86 ng/person/day, compared with our estimated 12,000 ng/person/day from daily oral ingestion of 2 L of drinking water. Data from other studies indicate that dermal absorption of other PAHs is not significantly higher than absorption of phenanthrene (Moody and Chu 1995; Sartorelli et al 1999; Van Rooij et al 1995). …”
Section: Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…On the basis of a maximum phenanthrene concentration of 6 μg/L in drinking water (Table 2) and a surface body area of 18,000 cm 2 , we calculated that 30 min of daily bathing or showering would result in a dermally absorbed phenanthrene dose of only 86 ng/person/day, compared with our estimated 12,000 ng/person/day from daily oral ingestion of 2 L of drinking water. Data from other studies indicate that dermal absorption of other PAHs is not significantly higher than absorption of phenanthrene (Moody and Chu 1995; Sartorelli et al 1999; Van Rooij et al 1995). …”
Section: Methodsmentioning
confidence: 79%
“…We did not estimate dermal exposure during bathing or showering because a ) data on dermal absorption of PAHs from aqueous matrices are scarce, b ) absorption of PAHs is highly dependent on the vehicle used in the tests, and c ) available information suggests that exposure from dermal absorption would be negligible compared with oral ingestion from drinking water. Specifically, Moody and Chu (1995) examined dermal absorption of 14 C-labeled phenanthrene in vitro in human skin and observed 24% absorption after exposure of 0.64 cm 2 skin for 24 hr to a 0.1 mL solution of 1 µg/mL phenanthrene. From this, an equilibrium constant in terms of partial pressure ( K p ) was determined (1.6 × 10 –3 cm/hr) (Moody and Chu 1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have confirmed soil matrix is an important factor in determining a pesticides' bioavailability (Umbreit et al 1986(Umbreit et al , 1988. Some authors have reported pesticides' bioavailability rates in dermal absorption from water (Wester et al 1987;Moody and Chu 1995). Also, there are publications about lung absorption of pesticides in work atmosphere (Chester 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to ultraviolet (UV) radiation above a threshold level can cause damage to the barrier properties of the skin and has been shown to increase the dermal penetration of small hydrophilic chemicals (Gelis et al, 2002). This is a problem because dermal absorption is a major source of chemical exposure in occupational and agricultural (Fenske and Elkner, 1990;Nielsen and Nielsen, 2000;Nomiyama et al, 2001) as well as recreational settings (Lindstrom et al, 1997;Moody and Chu, 1995;Xu et al, 2002). Sunscreen use should, therefore, help prevent this damage and reduce the absorption of undesirable penetrants.…”
Section: Introductionmentioning
confidence: 99%